P0022 Clinical characteristics of young Indonesian colorectal cancer patients: A preliminary study. (July 2015) - Kurniawan, A.; Lugito, N.P.H.; Yanto, T.A.; Wijaya, I.; Tjiang, M.M.; Setiadinata, R.; Sumantri, S.; Seto, E.
Abstract : Background: Colorectal cancer is generally a disease of people aged above 40 years. Controversies still exist regarding the clinical characteristics of colorectal cancer in young people. The aim of this study is to know the clinical characteristics of young patients with colorectal cancer at the Siloam General Hospital, Karawaci, Banten. Methods: 14 patients with a diagnosis of colorectal cancer from December 2013, to January 2014, in Siloam General Hospital were studied cross-sectionally. The symptoms and signs, family history of cancer, diabetes, and location of mass were collected and evaluated. Findings: Five (35.7%) cases of colorectal cancer were in patients aged below 40 years (young patients) and nine (64.3%) cases were in patients above 40 years (old patients). The most common symptom was constipation and bloody diarrhoea, occurring in 57.1% of young patients and in 42.9% of old patients. Constipation occurred in two young patients and six old patients, and bloody diarrhoea occurred in three young patients and three old patients. Two (14.2%) young patients had a history of cancer in the family, whereas none of the old patients had a family history of cancer. Regarding location of tumour in the colon, four (28.5%) patients had a tumour in the ascending colon; two of the cases in young patients and the remaining two cases in old patients. Three (21.7%) patients had a tumour in descending colon; two cases were in young patients and one was in an old patient. Eight (57.1%) patients had a tumour in the rectum; two of the cases were in young patients and six cases were in old patients. One young patient had diabetes, and one other young patient had positive Clostridium difficile antigen and toxin. Interpretation: Approximately 35.7% cases of colorectal cancer (CRC) in our hospital were in young patients. Two patients had a family history of cancer. The location of mass was not specific for young patients with colorectal cancer.